STRATEGI BRANDING SMK MELALUI KEMITRAAN DENGAN DUNIA USAHA DAN INDUSTRI (DUDI) - basori, Chamdan; Ahmad zainudin; Priyadi (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
Branding strategies for Vocational High Schools (SMK) are a crucial aspect in improving their image, competitiveness and attractiveness for prospective students and the industrial world. One effective approach is through partnerships with the World of Business and Industry (DUDI). This research aims to analyze the branding strategy implemented by SMK in building a positive image through collaboration with DUDI. The method used in this research is descriptive qualitative, literature study and case analysis of several vocational schools that have succeeded in building branding through strategic partnerships. The research results show that vocational school branding can be strengthened through internship programs, industrial project-based learning, competency certification recognized by the world of work, and digital-based promotions. The partnership with DUDI also plays a role in providing learning facilities that are more relevant to industry needs, thereby increasing public confidence in the quality of vocational school graduates. By implementing an effective branding strategy through a partnership with DUDI, SMK can strengthen its position as a vocational education institution that is oriented to the needs of the world of work.